A Brief Report on the Association between Dissociation during Sex and Condom Use Self-Efficacy among Women Residing in Domestic Violence Shelters. Issue 2 (2nd April 2020) - Cavanaugh, Courtenay; Kapij, Alexis
Abstract: Objective: Female survivors of intimate partner violence have greater risk for contracting HIV/STI's and experiencing dissociation. However, no studies have examined the association between dissociation and condom use self-efficacy in this population. This study explored whether dissociation during sex was negatively associated with condom use self-efficacy. Methods : Thirty-five women (88% African American) who were residing in domestic violence shelters in the United States completed questionnaires. Results: There was a negative correlation between dissociative experiences during sex and condom use self-efficacy, r = −0.62, n  = 35, p  < .01. Conclusions : Findings suggest that dissociation during sex interferes with abused women's condom use self-efficacy.